Sex-Specific Variations in Spatial Reference Memory Acquisition: Insights from a Comprehensive Behavioral Test Battery in C57BL/6JRj Mice. - Melgar-Locatelli, Sonia; Mañas-Padilla, María del Carmen; Gavito, Ana Luisa; Rivera-González, Patricia; Rodríguez-Pérez, Celia; Castilla-Ortega, María Estela; Castro-Zavala, Adriana (My University, 2023)
Sex differences in declarative memory are described in humans, revealing a female or a male advantage depending on the task. Specifically, spatial memory (i.e., spatial navigation) is typically most efficient in men. This sexual dimorphism has been replicated in male rats but not clearly in mice. In this study, sex differences in spatial memory were assessed in thirty-six C57BL/6 J mice (Janvier Labs; i.e., C57BL/6JRj mice), a widely used mouse substrain. Both male and female mice (12 weeks-old) were subjected to standard behavioral paradigms: the elevated plus maze, the open field test, the novel object and place tests, the forced swimming test, and the water maze test for spatial navigation. Across assessment, no sex differences were found in measures of locomotor activity, emotional and behavioral responses, and object and place recognition memories. In the water maze, male mice were faster in learning the platform location in the reference memory training and used more spatial strategies during the first training days. However, both sexes reached a similar asymptotic performance and performed similarly in the probe trial for long-term memory consolidation. No sex differences were found in the cued training, platform inversion sessions, or spatial working memory sessions. Hippocampal expression of the brain-derived neurotrophic factor was similar in both sexes, either in basal conditions or after performing the behavioral training battery. Importantly, female mice were not more variable than males in any measure analyzed. This outcome encourages the investigation of sex differences in animal models and the usefulness of including female mice in behavioral research.
Keywords: Memoria; Morris water maze; Object recognition; Females; Variability; BDNF